2005
DOI: 10.1158/1078-0432.ccr-04-1899
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Validation of the International Classification of Immunoglobulin M Gammopathies: A Survival Advantage for Patients with Immunoglobulin M Monoclonal Gammopathy of Undetermined Significance?

Abstract: Purpose: To verify the reliability of the new criteria for the diagnosis of IgM gammopathies recently proposed by an international panel of experts (Athens, 2002). Experimental Design: A retrospective series of 698 patients with IgM gammopathy was reviewed paying attention to symptoms, serum IgM concentration, bone marrow infiltration, blood cell count and clinical course. Four clinical entities can be identified: IgM monoclonal gammopathy of undetermined significance (IgM-MGUS), asymptomatic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 14 publications
1
46
0
2
Order By: Relevance
“…Indeed, a study by Baldini et al demonstrated that the overall survival of SWM patients is similar to that of the general population, making it more important that these patients be recognized clinically and avoid the risks of chemotherapy. 13 Of interest, Gobbi et al previously reported that the overall survival was similar to that of the general population, 14 attributable perhaps to closer medical surveillance resulting in better care of hypertension, diabetes, and other common disorders. It is therefore in the patient's best interest to recognize this entity so that these patients are not subjected to the risks of chemotherapy until evidence of progression to symptomatic WM.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Indeed, a study by Baldini et al demonstrated that the overall survival of SWM patients is similar to that of the general population, making it more important that these patients be recognized clinically and avoid the risks of chemotherapy. 13 Of interest, Gobbi et al previously reported that the overall survival was similar to that of the general population, 14 attributable perhaps to closer medical surveillance resulting in better care of hypertension, diabetes, and other common disorders. It is therefore in the patient's best interest to recognize this entity so that these patients are not subjected to the risks of chemotherapy until evidence of progression to symptomatic WM.…”
Section: Discussionmentioning
confidence: 98%
“…3 The criteria we use differ 2 and are based on subsequent studies. [12][13][14] We consider asymptomatic patients with an IgM M protein Ͻ 3 g/dL and lymphoplasmacytic infiltration less than 10% as IgM MGUS, and not WM. 2 Because these patients have a survival similar to the general population and require no therapy, they should not be erroneously labeled as having a malignancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, no evidence suggests that treatment of patients with smoldering/asymptomatic Waldenström macroglobulinemia provides a survival benefit compared with patients who begin therapy once symptoms occur. 34,35 Also, no evidence shows that delaying therapy until clinical progression occurs adversely affects the subsequent response to treatment. 36 Asymptomatic patients have a better quality of life without therapy, and withholding initial therapy limits their exposure to chemotherapeutic agents and possibly prevents development of drug resistance.…”
Section: Choice Of Initial Therapymentioning
confidence: 99%
“…Next, the natural history of each disease cohort was determined using sound epidemiological methods. 3,8,9,11,12,[14][15][16] As a result, we clearly know how to diagnose each of these entities accurately, and we also know the outcome of patients meeting the specific disease definition to assist with management and counseling. This approach to developing disease definitions is preferable to arbitrary criteria, in which the characteristics and outcome of patients meeting such criteria are unknown.…”
mentioning
confidence: 99%